Resterilization in cocoa (Theobroma cacao L.) somatic embryogenesispropagation to save contaminated embryos - Sulistyani Pancaningtyas; Cahya Ismayadi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
Somatic embryogenesis is a technique to produce primary embryos using tissue culture. Contamination in tissue culture can be caused by internal and external contaminant. Resterilization can be performed to save contaminated embryos. The aim of this research is to obtain resterilization method in cocoa micropropagation by tissue culture so that free bacterial explants can be obtained and embryogenic. This experiments used five clones of cocoa, namely Sulawesi 1, KW 514, ICCRI 05, ICCRI 03 and ICCRI 04. Embryogenic clusters in multiplication medium were used as explant. Sodium hypochloride was used as sterilant. Several factors were evaluated using randomized block complete design, i.e. contaminant level, concentration of sterilant and period of sterilant application. Results of resterilization methods showed no significant effect among several factors tested. Among those factors, low contamination level, 10% concentra tion of sterilant and no soaking showed the highest percentage of saving of contaminated embryos. There was different response among five cocoa clones in producing embryogenic explants when using combination of resterilization methods. Key words : Theobroma cacao, somatic embryogenesis, contamination, resterilization.